Pattern and Distribution of Scalp Injuries in Fatal Road Traffic Accidents in Rohtak Region of Haryana - An Autopsy based Study (Indian Journal of Forensic Medicine & Toxicology, 2020)
Head injuries are one of the leading cause of death worldwide as head being the most vulnerable part of thebody. The present study was performed on 100 cases of road traffic accidents in which head injuries werepresent. In this study, males clearly outnumbered females. The highest incidents were seen in the age group21 - 30 years (26%), followed by the age group 11 - 20 years (20%). In this study, special attention was givento the pattern and distribution of scalp injuries. Commonest scalp injury noticed in the present study wascontusion, seen in 33% of cases, followed by lacerated wounds in 30% cases.